2003
DOI: 10.2337/diacare.26.6.1781
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Metabolic Syndrome Among Omani Adults

Abstract: OBJECTIVE -To estimate the prevalence of the metabolic syndrome by age and sex in the RESEARCH DESIGN AND METHODS -We analyzed data from a cross-sectional survey conducted in 2001 containing a probability random sample of 1,419 Omani adults aged Ն20 years living in the city of Nizwa. The metabolic syndrome, defined by the ATP III, was defined as having three or more of the following abnormalities: waist circumference Ͼ102 cm in men and Ͼ88 cm in women, serum triglycerides Ն150 mg/dl (1.69 mmol/l), HDL choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
112
8
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(148 citation statements)
references
References 22 publications
24
112
8
4
Order By: Relevance
“…The same diagnostic approach was previously used in other Asian populations, namely the Omani from Saudi Arabia (31). A slightly higher proportion of Japanese-Brazilian men with metabolic syndrome are compatible with greater cardiovascular risk attributed to sex.…”
Section: Methodsmentioning
confidence: 99%
“…The same diagnostic approach was previously used in other Asian populations, namely the Omani from Saudi Arabia (31). A slightly higher proportion of Japanese-Brazilian men with metabolic syndrome are compatible with greater cardiovascular risk attributed to sex.…”
Section: Methodsmentioning
confidence: 99%
“…13 Both the World Health Organization (WHO) and the National Cholesterol Education Program (NCEP) Adult Treatment Panel III have published working definitions of the MetS, [14][15][16][17] and the prevalence rates of the MetS have been assessed in various populations around the world. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, little is known about the distribution of MetS among Aboriginal Canadians. The aim of this study was to estimate the prevalence of MetS and describe its characteristics between two Canadian Aboriginal groups (Native Indians and Inuit) compared to non-Aboriginal Canadians of predominantly European origin.…”
Section: Introductionmentioning
confidence: 99%
“…In Oman, Al Lawati et al (2003) [20] reported that the rate of Metabolic Syndrome(MS) was found to be 21% among Omanis adults ≥ 20 years of age according to the criteria of the US National Cholesterol Education Program (NCEP).…”
Section: Discussionmentioning
confidence: 99%